Proposição de técnicas e modelos de gestão para o esgotamento sanitário em áreas rurais brasileiras - Anderson Gomes da Silva (2017)
In 2013, the development of new public measures aimed at the sanitation sector was evidenced by the creation of the National Plan for Basic Sanitation - PLANSAB, which establishes national and macro-regional goals that aim at the universalization and improvement of the management of sanitation services in the country. In view of the lack of measures aimed at promoting basic sanitation in rural areas and their deficit situation interms of access to these services in the current scenario, the Plan proposes the elaboration of a program focused especially on the promotion of sanitation in these areas. This is the National Rural Sanitation Program - PNSR. In the context of the development of this program, the present research was developed to propose techniques and management models for the promotion of sanitation in Brazilian rural areas. For that, fifteen Brazilian communities from different regions of the country were used for representing different typologies of rural areas. These communities were characterized and had their current status of sanitation assessed through qualitative methodologies such as non-participant observation, semi-structured interviews, group interviews, "talking map", documentary and content analysis, all based on the so-called Grounded Theory. In it, data collection and analysis are done simultaneously with the researcher's attempts to develop theoretical explanatory structures about what is being researched. The Expert Panel technique was used to discuss the sanitary situation in question and strategies to promote sanitation services in these areas. An expert consultation was also carried out by means of an electronic questionnaire, which verified, through the AHP Method, which management models would best suit different operating scenarios of the sanitation service. Based on community characterization, literature review and questionnaire results, the proposal of techniques and management models for the communities was proposed. Different types of technologies were indicated, such as individual solutions without water supply (dispersed population and low availability of water), individual solutions with water suply (dispersed population and water availability) and collective wastewater treatment systems (population with water availability). The management models chosen varied between Social Organization, for the cases of solutions without water transport, and Shared Management for the others. Thus, the flexible nature of this research, whose analysis and solution proposition process can be replicated in order to serve as an instrument for decisionmaking with regard to the adoption of management models and sanitation technologies for Rural areas